Effect of Bacillus subtilis BS-Z15 metabolite mycosubtilin on body weight gain in mice - Yang, Jun; Zhao, Jing-Jing; Yue, Jun-Qi; Ma, Ming-Yue; Liu, Huan; Chen, Jia-Yi; Cao, Xi-Yuan; Li, Hao-Ran; Zhao, He-Ping; Yang, Yi; Zhao, Hui-Xin (Frontiers in Microbiomes, 2024)
Our previous study reported that the metabolite of Bacillus subtilis BS-Z15 n-butanol site could reduce body weight gain in mice, showing anti-obesity effects. This study further demonstrated the effects of purified mycosubtilin on the body weight gain and gut microbiota of Kunming mice. 30 male Kunming white mice were randomly selected into three groups at four weeks of age: Control (group A), gavage-administered with saline daily; n-butanol site treated (group B), gavageadministered with n-butanol site metabolites (90 mg/kg); and mycosubtilin treated (group C), gavage-administered with mycosubtilin (6 mg/kg). Different groups' gut microbiota compositions were analyzed using high-throughput sequencing technology. The results showed that the effects of mycosubtilin and n-butanol sites were consistent; the treatment groups showed a significant reduction in body weight gain as well as triglyceride and low-density lipoprotein contents as compared to the control group (P <0.05). Moreover, the size and contents of epididymal adipocytes were also significantly reduced (P <0.05), and the gavage administration of mycosubtilin could significantly increase the expression levels of lipolysis gene adipose triglyceride lipase (ATGL) in the mice liver. Mycosubtilin and n-butanol site treatments could significantly alter the composition of the gut microbiota as compared to the physiologic saline treatment. B. subtilis BS-Z15 metabolites may regulate weight gain primarily by mycosubtilin, according to these findings. The mycosubtilin might reduce weight gain in mice by regulating lipid metabolism, thereby reducing fat accumulation and altering the composition of gut microbiota.